A Study of the Relationship Between Tutor's Personality and Teaching Effectiveness: Does Culture Make A Difference? - Chan, Bobbie (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2002)
Good tutoring requires appropriate interpersonal and pedagogical skills. Tutor personality is a major factor affecting how tutors communicate and deals with students, and yet it is a largely unexplored context of distance education. Using the Chinese Personality Assessment Inventory (CPAI)* this paper examines how the personality of tutors’ affects their teaching effectiveness at a distance learning institution in Hong Kong. The results are compared to those reported by Chan (2001) in a similar study using the Myers-Briggs Type Indicator (MBTI). The results indicate that certain scales on the Chinese Tradition factor of the CPAI are significantly related to tutors’ teaching performance, and that the MBTI could not subsume all the CPAI scales. Future research with the CPAI should explore whether this Chinese Tradition factor is unique to the Chinese culture or whether it comprises elements of a universal domain useful in understanding key interpersonal aspects of personality that have been absent from Western personality inventories.